Al-MuwÄjahah bayn al-â€˜Urf wa al-SharÄ«â€™ah al-IslÄmÄ«yah fÄ« IndÅ«nÄ«sÄ«yÄ: Nadrah TÄrÄ«khÄ«yah fÄ« al-QÄnÅ«n al-JanÄâ€™i fÄ« Asia fÄ« al-Fatrah 1516-1688 - Yakin, Ayang Utriza (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2007)
Following the demise of the New order Regime in 1998, a period to become known as reformasi (reformation), the demand for the implementation of Islamic shari'ah became louder. Helped by the Regional Autonomy Laws of 1999, a number of regions in Indonesia demanded Islamic law to be implemented. Aceh was most adamant in its demand. At present, the implementation of Islamic shari'ah in Aceh has been provided with a legal basis by Law No. 44, 1999 and Law 18, 2001 on special Autonomy and the implementation of lslamic shari'ah in Aceh. The Regional Government of Nangroe Aceh Darussalam (NAD) has also issued a number of practical Regional Bylaras (Qanun) including the prohibition on drinking alcoholic beverages (khamar), regulated in Qanun No. 12/2003, the prohibition on gambling (maisir) in Qanun No. 13/2003, and the disallowance of illicit sex (khalwat) in Qanun No. 14/2003.DOI:Â 10.15408/sdi.v14i3.548